2014
DOI: 10.1002/hep.27233
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of B7 costimulation in obesity-related nonalcoholic steatohepatitis and metabolic dysregulation

Abstract: The low-grade inflammatory state present in obesity contributes to obesity-related metabolic dysregulation, including nonalcoholic steatohepatitis (NASH) and insulin resistance. Intercellular interactions between immune cells or between immune cells and hepatic parenchymal cells contribute to the exacerbation of liver inflammation and steatosis in obesity. The costimulatory molecules, B7.1 and B7.2, are important regulators of cell-cell interactions in several immune processes; however, the role of B7 costimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 43 publications
(114 reference statements)
2
46
0
Order By: Relevance
“…CD80/86 co-stimulate T cells through interaction with T cell surface CD28, which in turn upregulates cytotoxic T-lymphocyte-associated protein 4 (CTLA4) to dampen sustained T cell responses [119]. Surprisingly, genetic inactivation of CD80/86 in mice promoted IR and increased AT inflammation, likely due in part to reduced anti-inflammatory Treg frequency in AT [119, 120]. However, simultaneously injecting both CD80- and CD86-blocking antibodies into wild-type DIO mice improved insulin sensitivity with no obvious impact on splenic Tregs [120], suggesting that targeting a combination of CD80 and CD86 could inhibit T2D pathogenesis.…”
Section: Adipocytes Mimic Immune Cell Properties In Obesity/t2dmentioning
confidence: 99%
See 1 more Smart Citation
“…CD80/86 co-stimulate T cells through interaction with T cell surface CD28, which in turn upregulates cytotoxic T-lymphocyte-associated protein 4 (CTLA4) to dampen sustained T cell responses [119]. Surprisingly, genetic inactivation of CD80/86 in mice promoted IR and increased AT inflammation, likely due in part to reduced anti-inflammatory Treg frequency in AT [119, 120]. However, simultaneously injecting both CD80- and CD86-blocking antibodies into wild-type DIO mice improved insulin sensitivity with no obvious impact on splenic Tregs [120], suggesting that targeting a combination of CD80 and CD86 could inhibit T2D pathogenesis.…”
Section: Adipocytes Mimic Immune Cell Properties In Obesity/t2dmentioning
confidence: 99%
“…Surprisingly, genetic inactivation of CD80/86 in mice promoted IR and increased AT inflammation, likely due in part to reduced anti-inflammatory Treg frequency in AT [119, 120]. However, simultaneously injecting both CD80- and CD86-blocking antibodies into wild-type DIO mice improved insulin sensitivity with no obvious impact on splenic Tregs [120], suggesting that targeting a combination of CD80 and CD86 could inhibit T2D pathogenesis. Future work exploring possible differences between adipocyte and macrophage CD80/86 function, as well as expansion of studies to include the long list of known co-stimulators (iCOS, PD-1 etc.…”
Section: Adipocytes Mimic Immune Cell Properties In Obesity/t2dmentioning
confidence: 99%
“…The role of the CD80/CD86 – CD28 interaction in stimulating proliferation, survival, and memory programming of T cells has been extensively studied [25]. In obesity, CD80 and CD86 gene expression have been shown to be increased in obese human and mouse adipocytes [62, 105]. CD86+ dendritic cells were enriched in the liver and VAT of obese mice [19].…”
Section: Antigen-specific Processes In Irmentioning
confidence: 99%
“…T cell costimulation is important in APC-T cell communication, and these signals are often critical nodes in the regulation of both T reg and effector/ memory T conv activity and homeostasis [18,44,45]. Because the presence or absence of appropriate costimulatory signals likely influences the magnitude of adipose tissue inflammation in obesity, many recent studies have examined the role of costimulatory molecules in this process with somewhat mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have identified a beneficial role for costimulation in maintaining a T reg pool, both systemically and in adipose tissue, which is protective against obesity-induced inflammation and metabolic disease [5,13]. In many other instances, loss of costimulation has been shown to alter energy use and inflammation in animal models [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%